"Making an effort for the very elderly": The acceptability of a multidisciplinary intervention to retirement village residents. (1st August 2022) - Jung, Isabelle; Bloomfield, Katherine; Hikaka, Joanna; Tatton, Annie; Boyd, Michal
Abstract: The retirement village (RV) population is a growing one, with many residents having unmet healthcare needs. Despite this, there is a relative paucity of research in the RV community. We previously performed a randomised controlled trial (RCT) of a multidisciplinary (MD) nurse‐led community intervention versus usual care within 33 RVs in Auckland, New Zealand. Participant acceptability is an important aspect in assessing intervention feasibility and effectiveness. The aim of this current qualitative study was to assess the acceptability of the intervention in participating residents. Data were collected using semi‐structured interviews designed around the Theoretical Framework of Acceptability. Thematic analysis was undertaken using a general inductive approach. Of the 199 participants in the intervention arm of the original RCT, 27 were invited to take part in this qualitative study. Fifteen participants were recruited with a median age of 89 years, 10 were female and all were of European ethnicity. Participants were generally positive about the intervention and research processes. Three themes were identified: (1) participants' understanding of intervention aims and effectiveness; (2) the importance of older adult involvement and (3) level of comfort in the research process. Despite the MD intervention being deemed acceptable across several domains, results provided learning points for the future design of MD interventions in RV residents and older adults more generally. We recommend that future intervention studies incorporate co‐design methodologies which may improve the likelihood of intervention success.